A representação social de prática profissional para psicólogos clínicos da Grande Vitória/ES - Mendes, Flávio Martins de Souza (2012)
Over the last thirty years, the professionals of psychology have sought to meet their professional practices. It has done studies and discussions regarding paradigms that underpin the profession, practices and beliefs about the psychologist and practice. Among them, we see the relevance and importance of clinical psychology, however, few studies have been conducted with professionals involved in this area. The research aimed to investigate and analyze the social representation of practice for clinical psychologists in Grande Vitória/ES. Dimensional Analysis and Dynamics of Social Representations (Theory of Social Representations) was used to investigate the concepts that make up the practice. Eighteen active clinical psychologists in office were interviewed. We used the software ALCESTE analysis. We worked with the elements of the classes identified by Alceste to compose the dimensions of social representation. It was found that respondents constructed information about clinical psychology and practice before entering the course or early in training. The theories used in the clinic are important aspects of this approach. Attitudes towards practice are extremely favorable, and unfavorable when compared to the beliefs of the population or the medical practice, touching in identity aspects. As for the field, we recognized a split image into two: 1) Picture of the atributions and practices of classical clinical psychologist; 2) Picture of problems, changes and difficulties. It was possible to identify the social representation of practice for clinical psychologists, raising important for the field of clinical psychology and the theory of social representations issues.